Employee Performance Appraisal in the Transporter Section at BINTAN DISTRICT Hospital - M. Ramadhan; Mimi Syahfitri; Satriadi Satriadi; Raharani Putri; Tri Andini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Performance appraisal is a formal system used to evaluate employee performance so that it is in accordance with predetermined work standards. Evaluation of employee performance must be carried out openly, honestly and objectively. The aim of this research is to find out how the concept and research of employee performance in the BINTAN DISTRICT Regional Hospital section. This research is also expected to be able to provide benefits for the company to be used by managers or management departments to improve the concept of performance assessment. The data collection method in this research was collected by means of interviews with the person in charge and field coordinator. As well as using qualitative methods, the results of this research know the concept of performance assessment of employees in the Transporter section at the BINTAN DISTRICT Regional Hospital.